Proterozoic flood basalts from the Coppermine River area, Northwest Territories: isotope and trace element geochemistry - Dupuy, C.; Michard, A.; Dostal, J.; Dautel, D.; Baragar, W. R. A. (Canadian Journal of Earth Sciences, 1992)
The voluminous Proterozoic continental tholeiites of the Coppermine River province (Northwest Territories), which are coeval with the Mackenzie magmatic event (1.27 Ga old) and were emplaced over a short period of time (< 5 Ma), have trace element and Sr–Nd–Pb isotopic characteristics comparable to those of Phanerozoic flood basalts. The variations of the compositional parameters are inferred to be due to a mixing of at least two components: mantle and crust. In addition, the mantle component probably includes two end members. The first is a mantle plume, whereas the other represents the base of the continental lithosphere. The crustal component reflects contamination of the magma by Precambrian basement during its ascent to the surface.